2011
DOI: 10.1007/s00277-011-1371-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of red blood cell parameters and ferritin in predicting deferral due to low hemoglobin in whole blood donors

Abstract: Risk factors for deferral from red blood cell (RBC) donation due to low hemoglobin are not well defined. We analyzed in a large cohort of returning donors the prognostic value of RBC parameters and serum ferritin regarding low hemoglobin levels at the subsequent visit. Between 2004 and 2009, RBC indices and serum ferritin were recorded in 45,533 visits by 7,994 donors. In 689 instances, donation was deferred at the subsequent visit due to low hemoglobin levels (<123 g/l for female donors, <133 g/l for male don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…The Advisory Committee for Blood Safety and Availability noted that a uniform cutoff of 12.5 g/dl allowed ‘anemic’ men to donate while excluding normal women [17], conclusions supported by the analyses of large population-based datasets [18]. Although the RISE study found a high prevalence of iron deficiency (77%) in Hb-deferred donors [11 ⦾⦾ ], other recent analyses show generally poor prognostic value of ferritin in predicting anemia [19 ⦾ ] and of venous Hb values in predicting low ferritin [20]. The clear lesson from the accumulated evidence is that donor Hb is a lagging indicator and highly imperfect proxy for donor iron status, and that where the latter is of interest it should be directly measured.…”
Section: Identifying Low Iron In Blood Donors and Limited Value Of Hementioning
confidence: 99%
“…The Advisory Committee for Blood Safety and Availability noted that a uniform cutoff of 12.5 g/dl allowed ‘anemic’ men to donate while excluding normal women [17], conclusions supported by the analyses of large population-based datasets [18]. Although the RISE study found a high prevalence of iron deficiency (77%) in Hb-deferred donors [11 ⦾⦾ ], other recent analyses show generally poor prognostic value of ferritin in predicting anemia [19 ⦾ ] and of venous Hb values in predicting low ferritin [20]. The clear lesson from the accumulated evidence is that donor Hb is a lagging indicator and highly imperfect proxy for donor iron status, and that where the latter is of interest it should be directly measured.…”
Section: Identifying Low Iron In Blood Donors and Limited Value Of Hementioning
confidence: 99%
“…As ferritin testing is comparatively costly, various red blood cell (RBC) parameters have been proposed as markers for low ferritin/iron depletion (13) . Significant correlations between ferritin and RBC parameters were shown in these analyses, but no study has determined which marker is the most useful to identify donors at risk of developing anemia (13) .…”
mentioning
confidence: 99%
“…Significant correlations between ferritin and RBC parameters were shown in these analyses, but no study has determined which marker is the most useful to identify donors at risk of developing anemia (13) . …”
mentioning
confidence: 99%
See 2 more Smart Citations